Cord blood lead levels in newborns. - BEKİROĞLU, GÜLNAZ NURAL (My University, 1996)
Lead is ubiquitous in the human environment as a result of industrialization and children are particularly susceptible to leadÕs toxic effects. Several investigators have reported the relationship between low-level lead exposure and prematurity, altered fetal growth and postnatal neurobehavioral development. The current status of lead exposure is not well defined in Turkey. We present the preliminary results of a study in which we measured cord blood lead levels of 145 newborns. Cord blood lead levels were between 10 and 19.9 µg/dl in 14% and above 20µg/dl in 10% of the study population. Although we were unable to show any effect of these levels on the incidence of preterm deliveries, intrauterine growth status and the rate of miscarriages, further prospective studies are required to show the long-term effects of low-level lead exposure.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Biyoistatistik ve Tıp Bilişimi; Dahili Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; Biostatistics and Medical Informatics; Internal Medicine Sciences; Klinik Tıp (MED); Klinik Tıp; TIBBİ BİLİŞİM; TIP, GENEL & DAHİLİ; Clinical Medicine (MED); CLINICAL MEDICINE; MEDICAL INFORMATICS; MEDICINE, GENERAL & INTERNAL; Genel Sağlık Meslekleri; Patofizyoloji; Temel Bilgi ve Beceriler; Değerlendirme ve Teşhis; Dahiliye; Tıbbi Bilişim; Aile Sağlığı; Tıp (çeşitli); Genel Tıp; General Health Professions; Pathophysiology; Fundamentals and Skills; Assessment and Diagnosis; Internal Medicine; Health Informatics; Family Practice; Medicine (miscellaneous); General Medicine; Newborn; cord blood; lead